A study for efficacy and safety of ferric carboxymaltose versus iron sucrose in iron deficiency anemia among pregnant women in tertiary care hospital - Agrawal, Divyani; Masand, Deepa Lokwani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Anemia is one of the common manageable problem among the pregnant women worldwide, which contributes to maternal and perinatal mortality. This study aims to compare the efficacy and safety of intravenous ferric carboxymaltose with intravenous iron sucrose in treating anemia during pregnancy. Objective of this study was to compare safety and efficacy of intravenous ferric carboxymaltose with intravenous ferric sucrose in iron deficiency anemia during pregnancy. Methods: It’s an interventional prospective study conducted in Department of Obstetrics and Gynecology at NIMS, Jaipur, Rajasthan, India constituting of 100 pregnant women. Group 1- 50 pregnant women were treated with intravenous ferric carboxymaltose and Group 2: 50 pregnant women were treated with intravenous iron sucrose. Hemoglobin and serum ferritin levels were measured pre and post treatment with parenteral iron therapy. The efficacy of intravenous ferric carboxymaltose in comparison to intravenous iron sucrose was assessed. The evaluation of safety and tolerance with the parenteral therapy was also performed. Results: Anemia during pregnancy was more prevalent among the reproductive age group and in multiparous women. The mean rise in the hemoglobin level with ferric carboxymaltose was 2.92 gm/dl and with that of iron, sucrose was 1.08 gm/dl. The man rise in the serum ferritin levels with ferric carboxymaltose was 64.97ng/ml and with iron sucrose was 31.64 ng/ml. Ferric carboxymaltose was observed to be safer with no adverse events in comparison to the Iron sucrose which was related with adverse events among 03 pregnant women. Conclusions: Intravenous ferric carboxymaltose was more efficacious and safer in comparison to intravenous iron sucrose among pregnant women. Hence, ferric carboxymaltose is the drug of choice in treatment of iron deficiency anemia during pregnancy.